2021
DOI: 10.3916/c67-2021-07
|View full text |Cite
|
Sign up to set email alerts
|

Coping with distress among adolescents: Effectiveness of personal narratives on support websites

Abstract: Sharing, reading and responding to personal narratives on peer-to-peer support websites may provide adolescents with informational and emotional support to feel more confident in coping with stressful events. However, their use may also pose a threat to adolescents’ coping self-efficacy. Principles of expressive writing, social sharing of emotions, narrative persuasion and self-effects may provide insight in how these actions may both positively and negatively relate to coping self-efficacy. By using a cross-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Prior studies have found that victimized girls find in SNSs a space for immediate peer support, such as advice and information on how to deal with these painful experiences (Mariën et al, 2021), which seem to contribute to a greater vulnerability to problematic use of virtual social networks, in addition to the sense of immediacy provided by SNSs and the possibility of communicating with their peers in this uninterrupted space and time (Mariën et al, 2021). Other studies have also demonstrated that empathy and pro-sociability are the main assets of girls' virtual status and reputation (Fondevila et al, 2020;González & Maroto, 2018), which could explain why they tend to avoid aggressive behavior when victimized.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies have found that victimized girls find in SNSs a space for immediate peer support, such as advice and information on how to deal with these painful experiences (Mariën et al, 2021), which seem to contribute to a greater vulnerability to problematic use of virtual social networks, in addition to the sense of immediacy provided by SNSs and the possibility of communicating with their peers in this uninterrupted space and time (Mariën et al, 2021). Other studies have also demonstrated that empathy and pro-sociability are the main assets of girls' virtual status and reputation (Fondevila et al, 2020;González & Maroto, 2018), which could explain why they tend to avoid aggressive behavior when victimized.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, studies have revealed that girls, compared to boys, are more vulnerable to the negative consequences (psychological and emotional problems) of different expressions of aggressive behavior both online and offline (Baldry et al, 2017;Zhang et al, 2020). These particularly stressful interpersonal experiences may, in turn, prompt girls to turn to these virtual spaces for emotional relief and support (Mariën et al, 2021). Thus, the association between peer victimization and problematic use of SNSs may be stronger in girls than in boys (Liu et al, 2020).…”
Section: Gender As a Moderatormentioning
confidence: 99%
“…In this study we aim to apply narrative persuasion theories to peer-to-peer support websites. Readers on peer-to-peer support websites are motivated to look for informational and emotional support in others' personal narratives (Mariën et al, 2021;Welbourne et al, 2013). As a result, readers may become persuaded by these narratives to feel better about and become more confident in coping with a distressing event (Mariën et al, 2021).…”
Section: Narrative Persuasion and Personal Narratives On Peer-to-peer...mentioning
confidence: 99%
“…We assume that the effects of personal narratives on peer-to-peer support websites may be moderated by the same variables. Since readers come to peerto-peer support websites to find informational and emotional support (Mariën et al, 2021;Sun et al, 2014;Welbourne et al, 2013), they are likely to evaluate how others' narratives are relevant to themselves. The specific characteristics of forums on peer-to-peer support websites lead to personal narratives that are written from a first-person perspective.…”
Section: Moderating E Ect Of Identi Cation and Similaritymentioning
confidence: 99%
See 1 more Smart Citation